Dewey decimal classification and relative index. Volume 3, Schedules, 600-999 - Dewey, Melvil, 1851-1931.; Beall, Julianne, 1946-; Matthews, Winton E.; Mitchell, Joan S.; New, Gregory R. (Albany, N.Y. : Forest Press, a division of OCLC Online Computer Library Center, 1996)
Presents the full text of the Dewey Decimal Classification system, a general knowledge organization tool; featuring schedules from 600 through 900, with information on the use of the schedules.
Professional.
Professional
Keywords: Classification, Dewey decimal; Dewey Decimal Classification